Risk and protection of different rare protein-coding variants of complement component C4A in age-related macular degeneration - Seddon, Johanna M.; De, Dikha; Casazza, William; Cheng, Shun-Yun; Punzo, Claudio; Daly, Mark; Zhou, Danlei; Coss, Samantha L.; Atkinson, John P.; Yu, Chack-Yung (Frontiers in Genetics, 2024)
Age-related macular degeneration (AMD) is the leading cause of central vision loss in the elderly. One-third of the genetic contribution to this disease remains unexplained. We analyzed targeted sequencing data from two independent cohorts (4,245 cases, 1,668 controls) which included genomic regions of known AMD loci in 49 genes. At a false discovery rate <0.01, we identified 11 low-frequency AMD variants (minor allele frequency <0.05). Several of those variants were present in the complement C4A gene, including the replacement of the residues that contribute to the Rodgers-1/Chido-1 blood group antigens: [VDLL1207-1210ADLR (V1207A)] with discovery odds ratio (OR) =1.7, (P=3.2x10 -5 ) which was replicated in the UK Biobank dataset (3,294 cases, 200,086 controls, OR=1.52, P=0.037). A novel variant associated with reduced risk for AMD in our discovery cohort was P1120T, one of the four C4A-isotypic residues. Gene-based tests yielded aggregate effects of nonsynonymous variants in 10 genes including C4A, which were associated with increased risk of AMD. In human eye tissues, immunostaining demonstrated C4A protein accumulation in and around endothelial cells of retinal and choroidal vasculature, and total C4 in soft drusen. Our results indicate that C4A protein in the complement activation pathways may play a role in the pathogenesis of AMD.